2011
DOI: 10.1016/s0027-9684(15)30383-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Symptoms, Comorbidity, and Treatment for Major Depressive Disorder Among Black and White Adults

Abstract: Objective Racial differences in the clinical nature of major depressive disorder (MDD) could contribute to treatment disparities, but national data with large samples are limited. Our objective was to examine black-white differences in clinical characteristics and treatment for MDD from one of the largest, national community samples of US adults. Methods Non-Hispanic black and white adults (n = 32 752) from the 2001–2002 National Epidemiologic Survey on Alcohol and Related Conditions produced data on 1866 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 66 publications
2
55
1
Order By: Relevance
“…This is particularly important because the optimal design for studying the reciprocal associations is a longitudinal design [16][17][18]. Second, literature has provided inconsistent [14,15] and even unexpected findings [13,14,19]. If Blacks have more CMCs and with a lower prevalence of depression than Whites, we would expect to observe a stronger association between depressive symptoms and CMCs among Whites than Blacks, with each incremental increase in number of chronic medical conditions associated with a smaller increase in depressive symptoms among Blacks compared to Whites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important because the optimal design for studying the reciprocal associations is a longitudinal design [16][17][18]. Second, literature has provided inconsistent [14,15] and even unexpected findings [13,14,19]. If Blacks have more CMCs and with a lower prevalence of depression than Whites, we would expect to observe a stronger association between depressive symptoms and CMCs among Whites than Blacks, with each incremental increase in number of chronic medical conditions associated with a smaller increase in depressive symptoms among Blacks compared to Whites.…”
Section: Introductionmentioning
confidence: 99%
“…If Blacks have more CMCs and with a lower prevalence of depression than Whites, we would expect to observe a stronger association between depressive symptoms and CMCs among Whites than Blacks, with each incremental increase in number of chronic medical conditions associated with a smaller increase in depressive symptoms among Blacks compared to Whites. However, Hankerson and colleagues documented a stronger association between major depressive disorder (MDD) and hypertension, obesity, and liver disease among Blacks compared to Whites [19], and Assari found a positive cross-sectional association between MDD and cardiovascular diseases among Blacks that could not be replicated for Whites [13]. Further, using the National Survey of American Life (NSAL) data, Watkins, Assari, and JohnsonLawrence (2015) showed that lifetime MDD was associated with at least one CMC among Blacks, but not Whites [15].…”
Section: Introductionmentioning
confidence: 99%
“…While much is known about racial, ethnic and gender disparities in receipt of communitybased outpatient mental health care [21][22][23][24][25], little is known about whether these same disparities carry-over into jail settings. Some recent studies suggest that racial disparities in mortality rates are smaller in prison populations than in the general community population [26][27][28], for example, but research has yet to establish whether jails mirror similar racial and gender disparities that exist in community treatment for people with severe mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…1 Depression is associated with high rates of medical and psychiatric comorbidity, 2 poor physical health and functioning, 3 and increased risk of suicide. 4 Lifetime prevalence estimates of MDD range from 14% to 17% in the United States (U.S.).…”
mentioning
confidence: 99%